Does Media Stimulate Reform Efforts? - Ramalho, Rita (World Bank, Washington, DC, 2019)
This paper investigates to what extent media impacts political decisions. A viable practical approach to test the relationship between mass media and political actions is through the use of the World Bank’s Doing Business data, specifically, by assessing local media coverage of Doing Business and implementation of business regulatory reforms. The tested hypothesis is that countries with higher media coverage of Doing Business tend to carry out more business regulatory reforms, assuming one- and two-year lags between media coverage and reform implementation. To achieve this objective, the study put together a comprehensive data set that encompasses country-specific local media coverage of the Doing Business report in 190 economies. The study finds that local media coverage of Doing Business has a significant influence on regulators’ actions. First, the analysis shows that the number of local media articles tends to increase the probability of whether a country does any reform. Second, countries with greater media coverage of Doing Business indicators tend to have higher numbers of implemented reforms.